Using Fuzzy Logic for Evaluating the Level of Countries’ (Regions’) Economic Development - Stojić, Gordan (Panoeconomicus, 2012)
There are several divisions of countries and regions in the world. Besides geo-political divisions, there also are economic divisions. The most common economic division is the that on developed countries and the poor ones. These divisions are a consequence of the level of: GDP, GDP per capita, unemployment rate, industrial growth, and so on. The question is how to define a mathematical model based on which the following will be assessed: who is rich and who is poor, or who is economically developed and who is not? How the boundaries of transition from one category to another can be defined? This paper presents a model for evaluating the level of economic development of countries and regions using "fuzzy" logic. The model was tested on a sample of 19 EU member countries and aspirants for membership. Key words: Model, Evaluation, Economy development, Fuzzy sets. JEL: C52, E01, O11.